Effect of magnetic slot wedge on the performance of bulb tubular turbine generator. Issue 4 (22nd July 2020) - Qiu, Hongbo; Zou, Xutian; Fan, Xiaobin
Abstract : Purpose: Owing to the salient pole structure and stator slots of hydro-generator, the air gap magnetic field in the generator is unevenly distributed. High-frequency harmonic components contained in the inhomogeneous air gap magnetic field will have a negative impact on the generator performance. The purpose of this paper, therefore, is to improve the distribution of air gap magnetic field by using appropriate magnetic slot wedge, thereby improving the generator performance. Design/methodology/approach: Taking a 24 MW, 10.5 kV bulb tubular turbine generator as an example, the 2 D electromagnetic field model of the generator is established by finite element method. The correctness of the model is verified by comparing the finite element calculation data with the experimental data. The influences of the permeability and thickness of the magnetic slot wedge on the generator performance are studied. Findings: It is found that the intensity and harmonic content of the air gap magnetic field will change with the permeability of slot wedge and then the performance parameters of the generator will also change nonlinearly. The relationship between the eddy current loss, torque ripple, output voltage and other parameters of the generator and the permeability of slot wedge is confirmed. In addition, the variation of losses and torque with wedge thickness is also obtained. Originality/value: The influence mechanism of magnetic slot wedge on the performance of hydro-generator is revealed. The presented results give guidelines to selecting suitable magnetic slot wedge to improve generator performance.